Basal ganglia and restricted and repetitive behaviours in Autism Spectrum Disorders: current status and future perspectives. (12th May 2014) - Calderoni, S.; Bellani, M.; Hardan, A. Y.; Muratori, F.; Brambilla, P.
Abstract : This editorial offers a concise overview of the recent structural magnetic resonance imaging studies that evaluate the basal ganglia (BG) volumes in autism spectrum disorders (ASD). The putative relationship between the repetitive or stereotyped behaviours of ASD and BG volumes is also explored, with a focus on possible translational approaches.